Safety of working conditions during the COVID-19 pandemic at the Tucumã polycline in Rio Branco, Acre (Research, Society and Development, 2022)
Introduction: The main challenges that health professionals experience in facing the pandemic are the high transmissibility of the virus, the lack of Personal Protective Equipment - PPE, the work overload and the impact on mental health. Objective: To analyze the occupational safety measures offered to Policlínica Tucumã employees in their work activities during the COVID-19 pandemic, from March to December 2020 in Rio Branco-AC. Method: This is a cross-sectional study, with primary data. The sample consisted of 77 health professionals and they were interviewed at the health unit through a structured questionnaire. Results and Discussion: 83.1% reported that the unit did not offer mental health care, there was a significant adherence to PPE, and the mask (100%) was the most used item. In this sense, 87% of workers considered the distribution of PPE adequate, where 74% of them received training for the correct use, removal and disposal of this equipment. Of these professionals, 71.4% demonstrated feeling secure in the exercise of their work, 62.3% reported having direct contact with the patient and, therefore, most were afraid of personal contamination (48%) and family members (96.1%), however, 55.8% were not contaminated by COVID-19, showing a degree of satisfaction of “satisfied” (61%) regarding the safety measures adopted in the exercise of their work activities. Conclusion: In general, the health unit met all the necessary adjustments and measures to ensure the health of its workers and the population in general, also ensuring the provision of its health services.